O mosaico de habitats e a comunidade de mamíferos de médio e grande porte do Parque Nacional Cavernas do Peruaçu, norte de Minas Gerais - Guilherme Braga Ferreira (2008)
Environmental heterogeneity exerts powerful influences on the distribution of organisms, their interactions and their adaptations. Although Cerrados environmental heterogeneity is normally accepted as determinant to its diversity, in few occasions the use of these multiple habitats by the large mammal community has been evaluated. There are four basic ecological processes affecting population dynamics or community structure in complex landscapes (i. e. a habitat mosaic). Two of these processes habitat complementation (or complementarity) and supplementation are vey likely to be crucial for the large mammal community in the Cerrado and Caatinga. Studies which elucidate the influence of a habitat mosaic over the mammal community and how thedifferent species use these habitats are essential for the understanding of mammal species biology and ecology, for the development of conservation and management strategies and for planning future studies. Cavernas do Peruaçu National Park is located in southeastern Brazil in a landscape mosaic of dry forest and savanna. Richness, relative abundance and habitat use of the large mammal community was assessed using 50X50 cm track stations during 12 months in four different habitat types. A total of 215 records of 14 large mammals species was obtained. The estimated richness (Jackknife I) for the whole area was 16 ± 2.77 and for each habitat type it varied from 6 ± 0 to 13.18± 3.79. There was no significant difference between the Relative Abundance Indexes obtained in each habitat, neither in each season. The density of trees and shrubs did not affect the mammal community, although it was observed that the most structurally similar habitat types were also the most similar regarding the mammal community composition. The absence of significant differences in some evaluated parameters, added to the use of different habitat types, indicates that the habitat complementation/supplementation process is important for the mammal community in the study region, and probably for the whole Cerrado and Caatinga. Thus habitat heterogeneity is relevant for the studied community since the use of several habitats seems to be necessary for the acquisition of essential resources.